KERJASAMA PERTAHANAN INDONESIA-JERMAN MELALUI DEKLARASI JAKARTA TAHUN 2012-2016 - Titik Karomah; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to explain the interest of Indonesia cooperate with Germany on the field of defense by Jakarta Declaration in 2012-2016. Germany was chosen because it has excess in defense industry and plays an important role in the modernization of Indonesia’s defense equipment. The sign of MoU has been done between two countries since February 2012 which includes the purchased of Main Battle Tank Leopard, Marder, and fly training plane, education for soldier, joint military exercises along with defense industry development by Transfer of Technology.Data of this research was obtained from books, journals, articles, official documents and websites that support the hyphothesis. The author used Neorealism approach from Kenneth Waltz and nation-state level analyze. The theories used in this research concist of International Relations, the national interest by Daniel S. Papp, and security concept by Barry Buzan.The result of this research show that when cooperate with Germany there are benefits for Indonesia, this cooperation made a major impact on changes in military power possessed by the armed force of the Republic of Indonesia, mainly on the strenght of the military land defense equipments in the quality and quantity. Germany can fulfill need of Indonesia equipment force. Indonesian defense equipments getting better and military equipment which are sophisticated so that be a part of factors support Indonesia be the best position of strenght military in Southeast Asia.Keywords: Jakarta Declaration, International Relations, National Interest, Defense Cooperation, Modernization of Defense Equipments.